DYSTOCIA OUE TO CONJOINED TWIN MONSTER IN A MALABARI DOE - JAYAKUMAR, C; PROMOD, K; AZEEZ, ABDUL; PANICKER, SNEHA (The Indian Journal of Animal Reproduction, 2011)
Dystocia due to a conjoined twin monster in a Malabari doe has been reported.